Novel method for calculating installed capacity of stand-alone renewable energy systems - Tang-Tin Dao; Q. S. Vu; Van-Duc Phan; Minh Tran (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The use of new energy sources to replace traditional energy sources is the worldwide interest based on its irrefutable advantages, especially in regions where supply systems Power supply cannot reach. The devices installed capacity has a significant effect on the economy as well as on system operation. In this paper, formulate and solve the problem of optimizing installed capacity for devices (generators, charge controllers, storage, inverters) that are used in independent renewable energy systems. In illustrating this method of calculation, we apply it on a standalone system, i.e., it is not connected to the power supply grid.